Foreign aid and India's economic development - Rao, V. K. R. V.; Narain, Dharm; Institute of Economic Growth (London : Asia Pub. House, 1963)
This study examines the character, magnitude and organisation of foreign aid, the condition on which it has been received, the impact it has made on the economy, and the problems that it has given rise to. It also identifies the influence foreign aid has had on relations between India and the aid-giving countries or agencies and to what extent it has led to tensions.
Includes bibliographical footnotes and index.
lje 03/10/2018
Loans
Keywords: Economic assistance; Economic growth; India